Validation of smart textile electrodes for electrocardiogram monitoring in free-moving horses - Guidi, A.; Lanata, A.; Valenza, G.; Scilingo, E. P.; Baragli, P. (Journal of Veterinary Behavior Clinical Applications and Research, 2016)
This article focuses on the validation of smart textile electrodes used to acquire electrocardiogram (ECG) signals in horses in a comfortable and robust manner. The performance of smart textile electrodes is compared with standard Ag/AgCl electrodes in terms of the percentage of motion artifacts (MAs, the noise that results from the movement of electrodes against the skin) and signal quality. Seven healthy Standardbred mares were equipped with 2 identical electronic systems for the simultaneous collection of ECGs. One system was equipped with smart textile electrodes, whereas the second was equipped with standard Ag/AgCl electrodes. Each horse was then monitored individually in a stall for 1 hour, without any movement constraints. The ECGs were visually examined by an expert who blindly labeled the ECG segments that had been corrupted by MAs. Finally, the percentage of MAs (MA%) was computed as the number of samples of the corrupted segments over the whole length of the signal. The total MA% was found to be lower for the smart textiles than for the Ag/AgCl electrodes. Consistent results were also obtained by investigating MAs over time. These results suggest that smart textile electrodes are more reliable when recording artifact-free ECGs in horses at rest. Thus, improving the acquisition of important physiological information related to the activity of the autonomic nervous system, such as heart rate variability, could help to provide reliable information on the mood and state of arousal of horses